2021
DOI: 10.1016/j.ekir.2021.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Fibroblast Growth Factor 23 in Autosomal Dominant Polycystic Kidney Disease

Abstract: Introduction: Autosomal dominant polycystic kidney disease (ADPKD) is characterized by progressive cyst growth and a loss of functioning renal mass, but a decline in glomerular filtration rate (GFR) and onset of end-stage renal disease (ESRD) occur late in the disease course. There is therefore a great need for early prognostic biomarkers in this disorder. Methods: We measured baseline serum fibroblast growth factor 23 (FGF23) levels in 192 patients with ADPKD from the Consortium for Radiologic Imaging Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Three studies, including ours, have now measured intact FGF23, using a 2-site enzyme-linked immunosorbent assay (either Kainos or Immutopics), and shown that it is unequivocally elevated. [2][3][4] Moreover, it is the intact form of FGF23 in the blood that is associated with progression of kidney volume growth and decline in glomerular filtration rate, as shown previously in the HALT study, 3 and now by us in CRISP. 4 More work is needed to unravel this fascinating puzzle, as well as to determine whether the association of FGF23 with outcomes represents a causal effect.…”
Section: Author Contributionssupporting
confidence: 53%
See 1 more Smart Citation
“…Three studies, including ours, have now measured intact FGF23, using a 2-site enzyme-linked immunosorbent assay (either Kainos or Immutopics), and shown that it is unequivocally elevated. [2][3][4] Moreover, it is the intact form of FGF23 in the blood that is associated with progression of kidney volume growth and decline in glomerular filtration rate, as shown previously in the HALT study, 3 and now by us in CRISP. 4 More work is needed to unravel this fascinating puzzle, as well as to determine whether the association of FGF23 with outcomes represents a causal effect.…”
Section: Author Contributionssupporting
confidence: 53%
“…Indeed, severely polycystic livers were proved to produce and increase circulating FGF23 in ADPKD patients. 3 Overall, this study was very important, for it not only filled the gap by demonstrating what was not proved by the HALT-PKD Study which supported FGF23 use only in late ADPKD, 4 but also EI Ters et al showed predictive roles of FGF23 in ADPKD progression independent of chronic kidney disease. More mechanisms about FGF23 elevation in ADPKD will need to be studied.…”
mentioning
confidence: 73%
“… 19 A plethora of biomarkers have been shown to display associations with ADPKD disease progression, suggesting prognostic potential ( Table 1 ). 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 From an association standpoint, prognostic biomarkers should display a link with baseline eGFR and/or htTKV but also predict longitudinal growth in htTKV, decline in GFR, or time to kidney failure. Recent approaches to identify novel prognostic biomarkers have ranged from assessing disease severity based on the urine concentrating ability in patients after water deprivation 29 to looking at serum and urinary proteins, peptides, and metabolites.…”
Section: Emerging Biomarkersmentioning
confidence: 99%
“…To the Editor: We read the article "Prognostic Value of FGF23 in Autosomal Dominant Polycystic Kidney Disease" by El Ters and colleagues with great interest. 1 El Ters et al provided an important demonstration that serum FGF23 was a prognostic biomarker for kidney volume and renal outcomes or death in patients with early ADPKD. However, early elevation of FGF23 in ADPKD is complicated and remains inconclusive.…”
mentioning
confidence: 99%
“…Experimental studies in PKD rodents revealed high FGF23 expression in the cyst-lining epithelium of kidneys but not in bone. 1 As kidney FGF23 does not contribute to the elevation of its circulating levels in uremia, 2 there may be other sources of high FGF23 in early ADPKD. Because ADPKD is a systemic disease, we assume that PKD mutations in different organs and tissues may produce FGF23 and lead to serum FGF23 elevation in humans.…”
mentioning
confidence: 99%